VALIDATION OF THE CHINESE ACADEMIC SELF-EFFICACY SCALE FOR GRADUATE STUDENTS - Tianlin Xie; Fong Peng Chew; Teng Teng Yap, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Recent research has explored the academic self-efficacy of students in higher education and its impact on learning engagement. In graduate learning environments, academic self-efficacy is a key motivator influencing students’ motives, educational achievement, and self-directed study ability. However, the Chinese adaption of the Academic Self-Efficacy Scale for Graduate Students (ASES-G) has not been systematically validated, which limits the development of related research to some extent. Therefore, the primary aim of this study is to adapt the Academic Self-Efficacy Scale (ASES) into a Chinese context and to assess its validity and reliability for graduate students in China. In this study, the original ASES was first culturally adapted and translated, and then experts were invited to assess its content validity. A two-step method was implemented to evaluate validity and reliability based on this. Exploratory factor analysis and reliability analysis were conducted to evaluate the construct validity and internal consistency of the scale; thereafter, the split-half reliability was calculated to validate the scale’s stability further. This study employed IBM SPSS Statistics for statistical analysis, revealing a Cronbach’s alpha of 0.886, indicating high reliability. The findings in this study suggest that the Chinese ASES-G demonstrates good validity and reliability among Chinese graduate students, making it a valuable tool for evaluating academic self-efficacy in forthcoming higher education research.